A method for preparing a TiO2@Cu-ZIF-8 photodynamic antibacterial and food-preserving composite film and its application.
Patent Information
- Application Number
- CN202611244223.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-13
AI Technical Summary
针对现有技术中光动力保鲜包装材料存在的可见光利用率低、光动力材料易团聚、异质结构效率差、功能单一以及金属离子迁移安全性缺乏系统验证,存在耐药菌风险,直接接触式发挥作用等缺陷,本发明旨在提供一种可见光响应高效、结构稳定、多功能集成且安全可靠的光动力抗菌保鲜复合薄膜及其制备方法与应用
[0025]1.本发明通过原位合成方法使ZIF-8在TiO2纳米颗粒表面直接成核生长,将TiO2限域于ZIF-8的孔道结构之中,利用ZIF-8的高比表面积和骨架限域效应实现了对TiO2的锚定分散,从根源上避免了TiO2纳米颗粒因高表面能而自发团聚的技术难题。同时,通过Cu2+后合成取代掺杂,使Cu2+成功取代ZIF-8骨架中部分Zn2+的配位位点,在ZIF-8禁带中引入Cu2+缺陷能级,将材料的光响应范围从紫外区拓展至可见光区。本发明所述TiO2@Cu-ZIF-8复合材料在可见光照射下即可被高效激发,产生足量的光生电子-空穴对,从根本上摆脱了传统TiO2基光敏剂对紫外光源的依赖,使得光动力保鲜技术在实际储运环境(自然日光或普通LED白光)下的应用成为可能。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of food active packaging and nanocomposite materials technology, specifically relating to a method for preparing a TiO2@Cu-ZIF-8 photodynamic antibacterial and preservation composite film and its application. In particular, it relates to a composite preservation film that uses TiO2@Cu-ZIF-8 composite material as a photosensitizer excited by visible light to generate active oxygen (ROS) under visible light to achieve antibacterial function, its preparation method, and its application in fruit and vegetable preservation. Background Technology
[0002] Strawberries, with their vibrant color, unique flavor, and rich nutrition, are among the most consumed fresh berries globally. However, strawberries experience high levels of respiration and transpiration after harvest, and their thin, unprotected skin makes them highly susceptible to moisture loss, softening, and discoloration during post-harvest storage and transportation. Furthermore, their surface is prone to harboring foodborne pathogens such as Escherichia coli, Staphylococcus aureus, and Botrytis cinerea, which not only accelerate spoilage but also pose food safety risks, severely limiting their shelf life and market reach. Therefore, developing efficient, safe, and environmentally friendly strawberry preservation technologies has significant practical importance and broad market prospects.
[0003] Currently, strawberry preservation technologies mainly employ low-temperature storage, chemical preservative treatment, and modified atmosphere packaging. Low-temperature storage (0-4℃) is the primary physical preservation method to delay quality deterioration, but its preservation effect is limited, and its use alone is insufficient to meet the needs of long-distance transportation and long-term storage. While chemical preservatives (such as chlorine dioxide and 1-methylcyclopropene) have certain anti-corrosion and preservation effects, they face potential risks such as chemical residues and pathogen resistance, leading to increasingly stringent restrictions on their application. These traditional preservation technologies generally share common problems, such as the antibacterial effect relying on direct contact or release between the preservative and food, posing a safety risk of chemical migration into food and the development of drug-resistant bacteria; the preservation technologies are mostly passive protection, lacking the ability to actively kill contaminated pathogens; and the ability to regulate strawberry postharvest respiration metabolism and ethylene activity is limited. Therefore, developing a novel, non-contact, residue-free, non-drug-resistant, and actively bactericidal green preservation technology has become an urgent problem to be solved in the food preservation field.
[0004] In recent years, photodynamic inactivation (PDI) technology, as a novel non-thermal sterilization technology, has shown great application potential in the field of food preservation. PDI technology has significant advantages such as non-contact sterilization, no chemical residues, and low susceptibility to inducing microbial resistance, and is considered an ideal technical route to replace traditional chemical preservatives. However, existing PDI preservation technologies still have many technical problems, such as: ① the low photocatalytic efficiency of existing photosensitizers and insufficient visible light utilization; the band gap of anatase TiO2 is approximately 3.2 eV, and its photoexcitation can only respond to ultraviolet light with wavelengths below 385 nm, making it difficult to effectively exert photodynamic activity under visible light (especially sunlight or ordinary LED light sources), severely limiting its application in actual food storage and transportation environments; ZIF-8 has a band gap as high as approximately 5.15 eV, and can hardly generate photogenerated carriers under visible light irradiation, making it difficult to use as a photodynamic material alone. ② TiO2 nanoparticles have high surface energy, making them prone to aggregation during film formation, leading to a reduction in effective active sites and a significant decrease in photocatalytic activity. Furthermore, the direct composite strategy of TiO2 and ZIF-8 cannot effectively inhibit TiO2 aggregation, nor can it fully utilize the high specific surface area of ZIF-8 to disperse and anchor TiO2, resulting in limited improvement in the photocatalytic activity of the composite system. ③ Existing PDI preservation films are mostly limited to single antibacterial functions, lacking multi-dimensional control over the packaging atmosphere. Preserving climacteric fruits and vegetables such as strawberries requires not only inhibiting microbial growth but also effectively regulating the concentrations of oxygen, water vapor, carbon dioxide, and ethylene within the packaging to create a suitable preservation atmosphere. However, most reported PDI preservation films currently focus only on their antibacterial properties, with insufficient systematic research and optimization of gas barrier / permeability, ethylene removal capabilities, and packaging microenvironment control capabilities, making it difficult to meet the multi-functional packaging material requirements of high-breathing-intensity fruits and vegetables. ④ The migration safety of metal ions in existing photodynamic films lacks sufficient experimental verification. Packaging films containing metal nanofillers may pose a risk of metal ion migration during food contact. Although ZIF-8 itself is considered to have good biocompatibility, the introduction of Cu 2+ The lack of safety data regarding the migration behavior of doped ions in simulated food solutions and whether they meet national food safety standards severely hinders the transformation of such materials from laboratory research to practical applications.
[0005] In summary, the existing technology lacks a photodynamic antibacterial preservation composite film product and its preparation method that can simultaneously meet the following requirements: ① the photosensitizer has high photodynamic activity under visible light; ② the photosensitizer is uniformly dispersed in the film matrix without agglomeration; ③ the preservation film has multiple functions including antibacterial, ethylene removal and gas atmosphere regulation; ④ the metal ion migration meets food safety standards, there is no risk of generating drug-resistant bacteria, and it works actively without contact. Summary of the Invention
[0006] Technical Problem to be Solved: To address the aforementioned technical problems, the objective of this invention is to provide a method for preparing a TiO2@Cu-ZIF-8 photodynamic antibacterial and preservative composite film and its application. This composite film firstly confines TiO2 nanoparticles within the porous structure of ZIF-8 through an in-situ synthesis method, forming a TiO2@ZIF-8 heterojunction with tight interfacial contact, inhibiting TiO2 aggregation and promoting photogenerated carrier separation; then, through Cu… 2+ Partial Zn doping 2+ Introducing Cu into the ZIF-8 bandgap 2+ Defect energy levels extend the light response range of the material from the ultraviolet region to the visible light region. Finally, TiO2@Cu-ZIF-8 composite material is blended with gelatin and polyvinyl alcohol and cast into a film to prepare a composite preservation film with photodynamic antibacterial, ethylene removal, and gas atmosphere regulation functions. Addressing the shortcomings of existing photodynamic preservation packaging materials, such as low visible light utilization, easy aggregation of photodynamic materials, poor efficiency of heterogeneous structures, single function, lack of systematic verification of metal ion migration safety, risk of drug-resistant bacteria, and direct contact action, this invention aims to provide a photodynamic antibacterial preservation composite film with high visible light response, stable structure, multifunctional integration, and safety and reliability, as well as its preparation method and applications.
[0007] Technical solution: A TiO2@Cu-ZIF-8 photodynamic antibacterial and preservation composite film, comprising a TiO2@Cu-ZIF-8 photodynamic material dispersed phase and a continuous film matrix phase; the continuous film matrix phase provides mechanical support and film-forming properties for the photodynamic material, and imparts suitable gas barrier and permeability to the film; the TiO2@Cu-ZIF-8 photodynamic material dispersed phase, as a photosensitive functional unit, generates reactive oxygen species (ROS) with antibacterial and ethylene scavenging activities under visible light excitation, and the two work together to regulate the internal atmosphere of the packaging.
[0008] A method for preparing a TiO2@Cu-ZIF-8 photodynamic antibacterial and food-preserving composite film includes the following steps: Step 1. Preparation method of dispersed phase of TiO2@Cu-ZIF-8 photodynamic material Preparation of S1.TiO2@ZIF-8 composite material 2-Methylimidazole, triethanolamine, and anatase nano-TiO2 were dispersed in water to obtain a mixed solution. Zinc acetate dihydrate solution was then added, and the mixture was stirred at room temperature for 24 hours, aged for 12 hours, and centrifuged at 8000-10000 rpm for 10-15 minutes. The precipitate was washed and freeze-dried at -50℃ and a vacuum degree <10 Pa for 24 hours to obtain the TiO2@ZIF-8 composite material. In this step, Zn... 2+ZIF-8 crystals are formed by self-assembly with 2-methylimidazole through coordination bonds. ZIF-8 is a regular rhombic dodecahedral crystal with an average diameter of 400-500 nm. ZIF-8 provides a high specific surface area and a regular microporous structure, which provides confined space for loading TiO2 nanoparticles and inhibits TiO2 agglomeration. Its pore structure provides channels for the adsorption and diffusion of gas molecules (O2, CO2, C2H4).
[0009] Triethanolamine acts as a deprotonating agent to promote the deprotonation of 2-methylimidazole and also acts as a structure-directing agent to regulate the crystal growth of ZIF-8. When the amount of triethanolamine added is greater than 250 mL / L, the morphology of ZIF-8 will show an irregular square shape instead of a regular rhombic dodecahedron.
[0010] In the TiO2@ZIF-8 composite material, anatase nano-TiO2 (40nm particle size) serves as a nucleation site, encapsulated within the ZIF-8 crystal or embedded on its surface. On one hand, it acts as a photosensitizer, generating photogenerated electron-hole pairs under visible light excitation, and its high specific surface area and surface active sites provide a site for the adsorption and reaction of gas molecules. On the other hand, it forms a heterojunction interface with ZIF-8, promoting the spatial separation of photogenerated carriers, and the close contact between TiO2 and ZIF-8 provides a channel for the migration of photogenerated electrons from TiO2 to ZIF-8.
[0011] The addition amount of anatase nano-TiO2 is 0.5-5.5 g / L, preferably 0.5-4.5 g / L. When the addition amount is less than 0.5 g / L, the number of photodynamic functional units in the film is insufficient, and the amount of ROS generated under visible light excitation cannot effectively kill pathogenic microorganisms, the antibacterial activity does not reach the expected threshold, and the preservation effect is limited. When the addition amount is greater than 4.5 g / L, the TiO2 dispersion in the system is uneven, leading to stress concentration and deterioration of mechanical properties, while also reducing the ability of photodynamics to generate ROS.
[0012] S2. Copper ion substitution doping TiO2@ZIF-8 composite material was dispersed in water to obtain a TiO2@ZIF-8 composite material solution with a concentration of 7.5-9.0 g / L. Then, copper acetate monohydrate solution was added, and the mixture was stirred in the dark at 25℃ and 200 rpm for 6-18 h. After centrifugation at 8000-10000 rpm for 8-10 min, the precipitate was washed and freeze-dried at -50℃ and vacuum degree <10 Pa for 24 h to obtain TiO2@Cu-ZIF-8 composite material. The mass ratio of TiO2@ZIF-8 composite material to copper acetate monohydrate was 2:(0.5-1.5). The preferred concentration of TiO2@ZIF-8 composite material solution was 8.25 g / L.
[0013] Cu 2+ (Ionic radius 0.71 Å) and Zn 2+ Cu has a similar ionic radius (ionic radius 0.74 Å). 2+ It can pass through the surface pores of ZIF-8 and replace part of the Zn coordinated with 2-methylimidazole. 2+ This forms Cu-N coordination bonds. This substitution process introduces Cu into the band gap of ZIF-8. 2+ Defect energy levels extend the absorption spectrum of a material from the ultraviolet region to the visible light region.
[0014] Cu 2+ The Zn in the ZIF-8 framework was uniformly replaced by post-synthetic substitution doping. 2+ The coordination site of Cu forms a Cu-N coordination bond with the N atom of 2-methylimidazole, and the molar ratio of Cu to Zn is approximately 1:2. 2+ The role of doping in photodynamic systems is ① to introduce Cu into the ZIF-8 bandgap. 2+ Defect levels extend the photoresponse range of materials from the ultraviolet region to the visible light region, enabling the materials to generate ROS under visible light (natural sunlight or LED light) excitation; ② Defect levels act as electron traps, further suppressing the recombination of photogenerated electron-hole pairs; ③ Cu 2+ Doping slightly shrinks the lattice (shifts the (011) diffraction peak to the right), improving the structural stability of TiO2@Cu-ZIF-8 photodynamic material.
[0015] Step 2. Preparation of composite preservation film 1) Dissolve gelatin in water and stir at 45°C in a water bath until completely dissolved to obtain a gelatin solution. Separately, add polyvinyl alcohol to water and stir at 80°C in a water bath until completely dissolved to obtain a polyvinyl alcohol solution. Mix the gelatin solution and the polyvinyl alcohol solution at 45°C, add 0.8-1% glycerol (based on the total mass of gelatin and polyvinyl alcohol), and continue stirring for 10-15 minutes until homogeneous to obtain a mixed film solution. The mass ratio of gelatin to polyvinyl alcohol in the mixed film solution is 1:(1-3), preferably 1:2. In this step, gelatin provides excellent biocompatibility, film-forming properties, and biodegradability. Its active groups (-OH, -NH2, -C=O) on its molecular chain can interact with metal ions (Zn) in TiO2@Cu-ZIF-8. 2+ Cu 2+ Ti 4+It forms metallic coordination bonds, enhancing the interfacial bonding between the photodynamic material and the film matrix; it also provides film-forming properties, imparting flexibility and transparency to the film. Polyvinyl alcohol provides excellent mechanical strength and tensile properties, giving the film good gas (O2, CO2) barrier properties and water vapor permeability; its -OH groups form intermolecular hydrogen bonds with the -NH2 and -OH groups of gelatin, forming a dense and uniform cross-linked network structure. Glycerin, as a plasticizer, reduces the brittleness of the film and improves its flexibility. However, when the amount of glycerin added is greater than 1%, it will cause the film to become too sticky, making it difficult to use during use.
[0016] 2) Add 1-6 wt% TiO2@Cu-ZIF-8 composite material (based on the total mass of gelatin and polyvinyl alcohol) to the above mixed film solution, and stir and disperse at 45°C for 30-60 min to ensure that the photodynamic material is uniformly dispersed in the film-forming substrate solution; then allow it to stand to remove bubbles to obtain the film-forming solution. The preferred addition amount of TiO2@Cu-ZIF-8 composite material is 1-3%. When the addition amount is <1%, the amount of ROS generated under visible light excitation is insufficient to effectively kill pathogenic microorganisms; when the addition amount is >6%, the photodynamic material agglomerates in the film matrix, resulting in a decrease in the mechanical properties of the film, an increase in transmittance, insufficient shielding effect, and excessively low light transmittance.
[0017] 3) Pour the above film-forming solution evenly onto a horizontal casting platform mold and dry at a constant temperature of 37℃ for 24 hours to allow the solvent (water) to evaporate slowly and the film to form naturally. After drying, peel the film off the casting platform to obtain the TiO2@Cu-ZIF-8 photodynamic antibacterial and preservative composite film; its film thickness is 70-90μm.
[0018] The above-described TiO2@Cu-ZIF-8 photodynamic antibacterial and food preservation composite film is used in the preparation of food preservation materials. The working principle of this TiO2@Cu-ZIF-8 photodynamic antibacterial and food preservation composite film is as follows: (1) Light absorption and carrier excitation When the composite film is irradiated with visible light, the TiO2 component in the TiO2@Cu-ZIF-8 composite material absorbs ultraviolet-visible light, while the Cu component in the ZIF-8 framework absorbs the light. 2+ Defect levels absorb visible light, and the energy of the photons causes electrons in the valence band of the material to jump to the conduction band, forming photogenerated electron (e⁻)-hole (h⁺) pairs, where Cu 2+ The presence of defect energy levels significantly reduces the photoexcitation energy barrier of materials, making visible light excitation possible.
[0019] (2) Heterojunction effect At the interface of the TiO2-ZIF-8 heterojunction, photogenerated electrons in the conduction band of TiO2 migrate to the conduction band of ZIF-8, while photogenerated holes in the valence band of ZIF-8 migrate to the valence band of TiO2. This spatial separation effectively suppresses electron-hole recombination and prolongs carrier lifetime; Cu 2+ The defect energy level further acts as an electron trap, promoting carrier separation, thereby synergistically improving the utilization efficiency of photogenerated carriers.
[0020] (3) Generation of reactive oxygen species (ROS) Photogenerated electrons and holes that migrate to the material surface undergo redox reactions with oxygen (O2) and water molecules (H2O) adsorbed on the material surface, respectively, to generate the following reactive oxygen species: Photogenerated electrons reduce O2 to generate superoxide anions (•O2⁻); •O2⁻ is further protonated to generate hydrogen peroxide (H2O2); Photogenerated holes oxidize H2O or OH⁻ to generate hydroxyl radicals (•OH); Singlet oxygen is generated through energy transfer pathways. 1 O2).
[0021] The ROS released from the film surface into the internal environment of the packaging can be precisely controlled by a light switch.
[0022] (4) Photodynamic antibacterial mechanism The released ROS exerts its antibacterial effect through the following pathways: ① attacking unsaturated fatty acids in the microbial cell membrane, inducing lipid peroxidation and disrupting cell membrane integrity; ② penetrating the cell membrane and oxidizing proteins and nucleic acids, leading to irreversible inactivation of the microorganisms. This antibacterial mechanism is non-contact and does not rely on the release of chemical antibacterial agents, therefore it does not induce drug resistance in microorganisms.
[0023] (5) Ethylene removal The released ROS oxidizes and decomposes ethylene (C2H4) into CO2 and H2O, reducing the ethylene concentration in the packaging environment and delaying the ripening and senescence process of fruits and vegetables.
[0024] (6) Gas atmosphere control The introduction of photodynamic material particles into the film creates an appropriate microporous structure in the film matrix, giving the film suitable gas permeability. The permeability of the film to water vapor (WVP), oxygen (OP), and carbon dioxide (CDP) can be adjusted by the amount of photodynamic material added. Appropriate WVP can promptly remove excess moisture from the packaging, preventing the growth of pathogenic microorganisms in a high-humidity environment; appropriate OP and CDP can maintain a low-O2, suitable-CO2 preservation atmosphere inside the packaging, effectively inhibiting the respiration intensity of fruits and vegetables. Beneficial effects
[0025] 1. This invention utilizes an in-situ synthesis method to directly nucleate and grow ZIF-8 on the surface of TiO2 nanoparticles, confining TiO2 within the porous structure of ZIF-8. By leveraging the high specific surface area and framework confinement effect of ZIF-8, the anchoring and dispersion of TiO2 is achieved, fundamentally avoiding the technical challenge of spontaneous aggregation of TiO2 nanoparticles due to their high surface energy. Simultaneously, through Cu... 2+ Subsequent synthesis and substitution doping of Cu 2+ Successfully replaced part of the Zn in the ZIF-8 skeleton 2+ The coordination sites introduce Cu into the ZIF-8 band gap. 2+ The defect energy level extends the photoresponse range of the material from the ultraviolet region to the visible light region. The TiO2@Cu-ZIF-8 composite material described in this invention can be efficiently excited under visible light irradiation to generate sufficient photogenerated electron-hole pairs, fundamentally eliminating the dependence of traditional TiO2-based photosensitizers on ultraviolet light sources. This makes the application of photodynamic preservation technology in actual storage and transportation environments (natural sunlight or ordinary LED white light) possible.
[0026] 2. This invention combines TiO2@Cu-ZIF-8 composite material with a gelatin-polyvinyl alcohol film-forming substrate, and prepares a composite food preservation film via a casting method. The TiO2@Cu-ZIF-8 composite material is uniformly dispersed in the film-forming matrix without large-scale agglomeration, providing a uniformly distributed distribution of active sites to ensure the photodynamic activity of the film. The composite food preservation film of this invention achieves the following effects under visible light irradiation: ① Photodynamic antibacterial: Visible light excites TiO2@Cu-ZIF-8 to generate ROS, which destroys the microbial cell structure in a non-contact manner. The antibacterial rate against Escherichia coli and Staphylococcus aureus is over 99%. It does not rely on the release of chemical antibacterial agents, thus fundamentally avoiding the development of bacterial resistance. ② Ethylene removal: The ROS generated by the TiO2@Cu-ZIF-8 composite material oxidizes and decomposes ethylene into CO2 and H2O, reducing the ethylene concentration in the packaging and delaying the ripening and senescence of fruits and vegetables; ③ Gas atmosphere control: The introduction of TiO2@Cu-ZIF-8 composite material into the film forms an appropriate microporous structure, giving the film suitable gas permeability (WVP decreases, OP and CDP moderately increase), which can timely remove O2 and CO2 produced by the respiration of fruits and vegetables, creating an ideal preservation microenvironment with low oxygen and suitable carbon dioxide.
[0027] 3. The TiO2@Cu-ZIF-8 photodynamic antibacterial and preservative composite film of this invention achieves the purpose of non-contact active antibacterial action, while Zn under simulated food contact conditions. 2+ / Cu 2+Compliant with GB4806.7-2023 requirements, ensuring the biosafety of the composite film in actual food contact applications; strawberry preservation tests verified that strawberries treated with TiO2@Cu-ZIF-8 photodynamic antibacterial preservation composite film maintained good freshness for 7 days at room temperature, with a preservation effect significantly better than that of TiO2@ZIF-8 composite film treatment and composite film treatment made by physical blending of TiO2@ZIF-8 / Cu-ZIF-8. This provides a safe, efficient, and environmentally friendly new technical solution for postharvest storage and preservation of fruits and vegetables with high respiration rates and easy perishability. Attached Figure Description
[0028] Figure 1 The images show the SEM images of ZIF-8, TiO2@ZIF-8, and TiO2@Cu-ZIF-8, as well as the elemental distribution surface scan of TiO2@Cu-ZIF-8. Here, a, c, and e represent the SEM images of ZIF-8, TiO2@ZIF-8, and TiO2@Cu-ZIF-8 at 50,000 magnification, respectively; b, d, and f represent the SEM images of ZIF-8, TiO2@ZIF-8, and TiO2@Cu-ZIF-8 at 100,000 magnification, respectively; and g, h, i, j, k, and l represent the total elemental distribution, Zn elemental distribution, Cu elemental distribution, Ti elemental distribution, O elemental distribution, and N elemental distribution of TiO2@Cu-ZIF-8, respectively. Figure 2 The images show surface SEM images and cross-sectional views of GP, GP / Z, GP / TZ, and GP / TCZ at different magnifications. Here, a, d, g, and i represent surface SEM images of GP, GP / Z, GP / TZ, and GP / TCZ at 500 magnification, b, e, h, and k represent surface SEM images of GP, GP / Z, GP / TZ, and GP / TCZ at 1000 magnification, and c, f, i, and l represent cross-sectional views of GP, GP / Z, GP / TZ, and GP / TCZ. Figure 3 The reactive oxygen species (ROS) generation levels of the composite materials and their thin film samples are given by: a represents the ROS generation levels of the blank control, ZIF-8, TiO2+ZIF-8, TiO2@ZIF-8, TiO2@Cu-ZIF-8 (L), TiO2@Cu-ZIF-8 (D), and Cu-ZIF-8; b represents the ROS generation levels of the blank control, GP, GP / Z, GP / TZ, and GP / TCZ. Figure 4The antibacterial activity of the composite materials and their film samples is represented by a, where a represents the effect of blank control, ZIF-8, TiO2@ZIF-8, Cu-ZIF-8, TiO2@Cu-ZIF as material samples, and GP, GP / Z, GP / TZ+CZ, and GP / TCZ as film samples on the growth of Escherichia coli, Staphylococcus aureus, and Botrytis cinerea; b represents the inhibition rate of blank control, ZIF-8, TiO2@ZIF-8, Cu-ZIF-8, and TiO2@Cu-ZIF on Escherichia coli, Staphylococcus aureus, and Botrytis cinerea; and c represents the inhibition rate of GP, GP / Z, GP / TZ+CZ, and GP / TCZ on Escherichia coli, Staphylococcus aureus, and Botrytis cinerea. Figure 5 The changes in appearance quality of strawberries in the Control group, GP group, GP / Z group, GP / TZ group, GP / TZ+CZ-D group, GP / TZ+CZ-L group, GP / TCZ-D group, and GP / TCZ-L group during storage. Detailed Implementation
[0029] The present invention will be described in detail below with reference to embodiments, but the embodiments of the present invention are not limited thereto. Unless otherwise specified, the experimental methods used in the embodiments are conventional methods; the materials and reagents used, unless otherwise specified, are commercially available. Those skilled in the art should understand that the specific embodiments described herein are only for explaining the present invention and are not intended to limit the present invention.
[0030] The organic ligands and metal salts used in the embodiments of this invention were all purchased from Aladdin Biochemical Technology Co., Ltd. (Shanghai), China; Fangda Tongzheng Chemical Co., Ltd. (Tianjin), China; and Beichen Fangzheng Reagent Factory (Tianjin), China.
[0031] Example 1 A method for preparing TiO2@ZIF-8 composite material includes the following steps: 821 mg of 2-methylimidazole (2-MI), 5.2 mL of triethanolamine (TEA), and 60 mg of anatase nano-TiO2 (particle size 40 nm) were uniformly dispersed in 20 mL of deionized water to prepare solution A. Separately, 220 mg of zinc acetate dihydrate (Zn(CH3COO)2·2H2O) was dissolved in 3 mL of deionized water to prepare solution B. Solution B was slowly added to solution A and stirred at 25 °C for 24 h, followed by aging for 12 h. After the reaction was completed, the precipitate was collected by centrifugation at 9000 rpm for 15 min, washed three times with deionized water, and freeze-dried at -50 °C and vacuum degree <10 Pa for 24 h to obtain TiO2@ZIF-8 composite material. Example 2
[0032] A method for preparing a TiO2@Cu-ZIF-8 composite material includes the following steps: 330 mg of the TiO2@ZIF-8 composite material prepared in Example 1 was uniformly dispersed in 40 mL of deionized water to prepare solution C. Separately, 154 mg of copper acetate monohydrate (Cu(CH3COO)2·H2O) was dissolved in 3 mL of deionized water to prepare solution D. Solution D was slowly added dropwise to solution C, and the mixture was stirred in the dark at 25 °C and 200 rpm for 12 h. After the reaction was complete, the precipitate was collected by centrifugation at 9000 rpm for 10 min, washed three times with deionized water, and freeze-dried at -50 °C and a vacuum degree <10 Pa for 24 h to obtain the light blue TiO2@Cu-ZIF-8 composite material.
[0033] The microstructure of ZIF-8 material, TiO2@ZIF-8 composite material and TiO2@Cu-ZIF-8 composite material was observed by scanning electron microscopy, and the elemental distribution of TiO2@Cu-ZIF-8 composite material was analyzed by energy dispersive X-ray spectroscopy (EDX).
[0034] like Figure 1 a and Figure 1 As shown in b, the ZIF-8 material exhibits a regular rhombic dodecahedral shape with a smooth surface and sharp edges, and an average diameter of approximately 400-500 nm. This indicates that the present invention successfully synthesized ZIF-8 crystals with good crystallinity and regular morphology using a room-temperature stirring method. Figure 1 c and Figure 1 As shown in Figure d, the TiO2@ZIF-8 composite material retains the rhombic dodecahedral morphology of ZIF-8 crystals, but interconnected TiO2 nanoparticles appear on the crystal surface, confirming that TiO2 has successfully combined with ZIF-8 material to form the TiO2@ZIF-8 composite material. Figure 1 e and Figure 1 f indicates that the TiO2@ZIF-8 composite material, when doped with Cu... 2+ The resulting TiO2@Cu-ZIF-8 composite material still retains the rhombic dodecahedral morphology, but the crystal surface becomes rougher, and the edges show a certain degree of gelatinization. The average diameter increases with Cu content. 2+ The addition of Cu slightly reduced the amount of Cu, so this morphological change indicates that Cu... 2+ During the doping process, the organic linker ligands on the ZIF-8 surface rearranged, and Cu... 2+ Through the surface channels of ZIF-8, a portion of Zn was successfully replaced. 2+ It connects with an organic ligand to form a Cu-ZIF-8 structure. For example... Figure 1 g、 Figure 1 h、 Figure 1 i、 Figure 1j、 Figure 1 k、 Figure 1 As can be seen, the surface of the TiO2@Cu-ZIF-8 composite material contains five elements—Zn, Cu, Ti, O, and N—which are uniformly distributed. Among these, Zn and N elements originate from the ZIF-8 framework (Zn...). 2+ (Coordination with 2-methylimidazole), Ti and O elements are derived from TiO2 nanoparticles, and Cu element is derived from post-synthesized substituted Cu. 2+ Therefore, in the TiO2@Cu-ZIF-8 composite material, TiO2 is uniformly distributed in the channels of ZIF-8 or embedded on the crystal surface without obvious agglomeration, while Cu... 2+ It uniformly replaced part of the Zn. 2+ Sites, two dopants (TiO2 and Cu) 2+ The uniformly distributed active sites in the ZIF-8 crystal structure provide a uniformly distributed basis for constructing efficient heterojunctions and improving photocatalytic activity in the composite system. Example 3
[0035] A method for preparing a TiO2@Cu-ZIF-8 photodynamic antibacterial and food-preserving composite film includes the following steps: Take 330 mg of gelatin and add it to 16.6 mL of deionized water. Stir at 600 rpm in a 45°C water bath until completely dissolved to obtain a gelatin solution. Separately, take 660 mg of polyvinyl alcohol and add it to 33.3 mL of deionized water. Stir at 600 rpm in an 80°C water bath until completely dissolved to obtain a polyvinyl alcohol solution. Mix the gelatin solution and the polyvinyl alcohol solution at 45°C, add 9.9 mg of glycerol, and continue stirring at 600 rpm for 10 min until homogeneous. Obtain the mixed film solution. Add 36 mg of TiO2@Cu-ZIF-8 composite material to the mixed film solution, sonicate for 20 min, and then stir and disperse at 600 rpm in a 45°C water bath for 30 min to ensure that the composite material is uniformly dispersed in the film-forming substrate solution. Then allow it to stand to remove bubbles to obtain the film-forming solution. The film-forming solution was poured evenly onto a horizontal casting platform mold and dried at a constant temperature of 37°C for 24 hours to allow the solvent to evaporate slowly and the film to form naturally. After drying, the film was peeled off from the casting platform to obtain the TiO2@Cu-ZIF-8 photodynamic antibacterial and food-preserving composite film. Comparative Example 1
[0036] The difference between this comparative example and Example 3 is that the TiO2@Cu-ZIF-8 composite material is not added, as detailed below: A method for preparing a gelatin-polyvinyl alcohol composite film includes the following steps: Take 330 mg of gelatin and add it to 16.6 mL of deionized water. Stir at 600 rpm in a 45°C water bath until completely dissolved to obtain a gelatin solution. Separately, take 660 mg of polyvinyl alcohol and add it to 33.3 mL of deionized water. Stir at 600 rpm in an 80°C water bath until completely dissolved to obtain a polyvinyl alcohol solution. Mix the gelatin solution and polyvinyl alcohol solution at 45°C, add 9.9 mg of glycerol, and continue stirring at 600 rpm for 10 minutes until homogeneous. Obtain the film-forming solution. Pour the film-forming solution evenly onto a horizontal casting platform mold and dry at 37°C for 24 hours to allow the solvent to evaporate slowly and the film to form naturally. After drying, peel the film off the casting platform to obtain the gelatin-polyvinyl alcohol composite film. Comparative Example 2
[0037] The difference between this comparative example and Example 3 is that the TiO2@Cu-ZIF-8 composite material is replaced with TiO2@ZIF-8 composite material, as detailed below: A method for preparing a TiO2@ZIF-8 photodynamic antibacterial and food-preserving composite film includes the following steps: Take 330 mg of gelatin and add it to 16.6 mL of deionized water. Stir at 600 rpm in a 45°C water bath until completely dissolved to obtain a gelatin solution. Separately, take 660 mg of polyvinyl alcohol and add it to 33.3 mL of deionized water. Stir at 600 rpm in an 80°C water bath until completely dissolved to obtain a polyvinyl alcohol solution. Mix the gelatin solution and the polyvinyl alcohol solution at 45°C, add 9.9 mg of glycerol, and continue stirring at 600 rpm for 10 min until homogeneous. Obtain the mixed film solution. Add 36 mg of TiO2@ZIF-8 composite material to the mixed film solution, sonicate for 20 min, and then stir and disperse at 600 rpm in a 45°C water bath for 30 min to ensure that the composite material is uniformly dispersed in the film-forming substrate solution. Then allow it to stand to remove bubbles to obtain the film-forming solution. The film-forming solution was poured evenly onto a horizontal casting platform mold and dried at a constant temperature of 37°C for 24 hours to allow the solvent to evaporate slowly and the film to form naturally. After drying, the film was peeled off from the casting platform to obtain the TiO2@ZIF-8 photodynamic antibacterial and fresh-keeping composite film. Comparative Example 3
[0038] The difference between this comparative example and Example 3 is that the TiO2@Cu-ZIF-8 composite material is replaced with ZIF-8 material, as detailed below: A method for preparing a ZIF-8 composite thin film includes the following steps: 821 mg of 2-methylimidazole (2-MI) and 5.2 mL of triethanolamine (TEA) were uniformly dispersed in 20 mL of deionized water to prepare solution A; 220 mg of zinc acetate dihydrate (Zn(CH3COO)2·2H2O) was dissolved in 3 mL of deionized water to prepare solution B; solution B was slowly added to solution A and stirred at 25 °C for 24 h, followed by aging for 12 h. After the reaction was completed, the precipitate was collected by centrifugation at 9000 rpm for 15 min, washed three times with deionized water, and freeze-dried at -50 °C and vacuum degree <10 Pa for 24 h to obtain ZIF-8 material; Take 330 mg of gelatin and add it to 16.6 mL of deionized water. Stir at 600 rpm in a 45°C water bath until completely dissolved to obtain a gelatin solution. Separately, take 660 mg of polyvinyl alcohol and add it to 33.3 mL of deionized water. Stir at 600 rpm in an 80°C water bath until completely dissolved to obtain a polyvinyl alcohol solution. Mix the gelatin solution and polyvinyl alcohol solution at 45°C, add 9.9 mg of glycerol, and continue stirring at 600 rpm for 10 min until homogeneous. Obtain a mixed film solution. Add 36 mg of ZIF-8 material to the mixed film solution, sonicate for 20 min, and then stir and disperse at 600 rpm in a 45°C water bath for 30 min to ensure that the composite material is uniformly dispersed in the film-forming substrate solution. Then allow it to stand to remove bubbles to obtain a film-forming solution. Pour the film-forming solution evenly onto a horizontal casting platform mold and dry at 37°C for 24 h to allow the solvent to evaporate slowly and the film to form naturally. After drying, peel the film off the casting platform to obtain the ZIF-8 composite film.
[0039] The surface features and cross-sectional microstructure of the composite films prepared in Example 3 and Comparative Examples 1-3 were observed using a scanning electron microscope. The TiO2@Cu-ZIF-8 photodynamic antibacterial and food-preserving composite film prepared in Example 3 was designated as GP / TCZ, the gelatin-polyvinyl alcohol composite film prepared in Comparative Example 1 was designated as GP, the TiO2@ZIF-8 photodynamic antibacterial and food-preserving composite film prepared in Comparative Example 2 was designated as GP / TZ, and the ZIF-8 composite film prepared in Comparative Example 3 was designated as GP / Z.
[0040] like Figure 2 a, Figure 2 d、 Figure 2 g and Figure 2As shown in j, the GP surface exhibits different degrees of texture structure, which is due to the microphase separation of gelatin and polyvinyl alcohol during the drying process. After incorporating ZIF-8 material, TiO2@ZIF-8 composite material and TiO2@Cu-ZIF-8 composite material, respectively, the texture degree of the GP / Z, GP / TZ and GP / TCZ composite film surfaces was not significantly aggravated compared with GP, indicating that the introduction of these materials did not cause significant damage to the original film structure of GP, indicating that there is good macroscopic compatibility among the components.
[0041] like Figure 2 b、 Figure 2 e Figure 2 h and Figure 2 As shown in k, all film samples exhibited relatively smooth surface morphology under high magnification, and no large-scale agglomeration or aggregated particles of photodynamic materials were observed. This result indicates that ZIF-8 material, TiO2@ZIF-8 composite material, and TiO2@Cu-ZIF-8 composite material can all be uniformly dispersed in the GP film matrix. This fully demonstrates that the introduction of TiO2@Cu-ZIF-8 composite material into the GP film matrix described in Example 3 can ensure the photodynamic activity and mechanical properties of the composite film, ensure that the TiO2@Cu-ZIF-8 composite material is uniformly distributed in the film to generate sufficient and uniformly distributed active oxygen, and avoid stress concentration and mechanical property deterioration caused by filler agglomeration.
[0042] like Figure 2 c. Figure 2 f、 Figure 2 i and Figure 2 As shown in Figure 1, the cross-sectional morphology results indicate that the average thicknesses of GP, GP / Z, GP / TZ, and GP / TCZ are 81.0 μm, 81.0 μm, 89.3 μm, and 70.1 μm, respectively. The film thickness is uniform and controllable. Moreover, the TiO2@Cu-ZIF-8 photodynamic antibacterial and preservative composite film prepared in Example 3 has the smallest thickness, indicating that Cu... 2+ The formation of metal coordination bonds after doping enhances the densification of the membrane matrix. Furthermore, the TiO2@ZIF-8 photodynamic antibacterial and preservation composite film described in Comparative Example 2 has the largest thickness, which may be related to the porosity effect generated by the TiO2@ZIF-8 composite particles in the membrane matrix. In summary, the incorporation of ZIF-8 material, TiO2@ZIF-8 composite material, and TiO2@Cu-ZIF-8 composite material has a relatively small impact on the film thickness; their thicknesses are all within the same order of magnitude, ensuring the comparability of subsequent performance test results. This also demonstrates that the TiO2@Cu-ZIF-8 photodynamic antibacterial and preservation composite film of this invention possesses microstructural characteristics of uniform dispersion of photodynamic materials, tight interfacial bonding, and controllable uniform thickness, providing a reliable structural guarantee for achieving efficient, stable, and safe photodynamic antibacterial and preservation functions in practical fruit and vegetable preservation applications. Comparative Example 4
[0043] This comparative example demonstrates the preparation method of the Cu-ZIF-8 composite material, and the specific steps are as follows: 821 mg of 2-methylimidazole (2-MI) and 5.2 mL of triethanolamine (TEA) were uniformly dispersed in 20 mL of deionized water to prepare solution A; 220 mg of zinc acetate dihydrate (Zn(CH3COO)2·2H2O) was dissolved in 3 mL of deionized water to prepare solution B; solution B was slowly added to solution A and stirred at 25 °C for 24 h, followed by aging for 12 h. After the reaction was completed, the precipitate was collected by centrifugation at 9000 rpm for 15 min, washed three times with deionized water, and freeze-dried at -50 °C and vacuum degree <10 Pa for 24 h to obtain ZIF-8 material; 330 mg of ZIF-8 composite material was uniformly dispersed in 40 mL of deionized water to prepare solution C. Separately, 154 mg of copper acetate monohydrate (Cu(CH3COO)2·H2O) was dissolved in 3 mL of deionized water to prepare solution D. Solution D was slowly added dropwise to solution C, and the mixture was stirred in the dark at 25 °C and 200 rpm for 12 h. After the reaction was complete, the precipitate was collected by centrifugation at 9000 rpm for 10 min, washed three times with deionized water, and freeze-dried at -50 °C and a vacuum degree <10 Pa for 24 h to obtain the Cu-ZIF-8 composite material. Comparative Example 5
[0044] The difference between this comparative example and Example 3 is that the TiO2@Cu-ZIF-8 composite material is replaced with Cu-ZIF-8 composite material and TiO2@ZIF-8 composite material, as detailed below: A method for preparing a TiO2@ZIF-8 / Cu-ZIF-8 composite thin film includes the following steps: Take 330 mg of gelatin and add it to 16.6 mL of deionized water. Stir at 600 rpm in a 45°C water bath until completely dissolved to obtain a gelatin solution. Separately, take 660 mg of polyvinyl alcohol and add it to 33.3 mL of deionized water. Stir at 600 rpm in an 80°C water bath until completely dissolved to obtain a polyvinyl alcohol solution. Mix the gelatin solution and the polyvinyl alcohol solution at 45°C, add 9.9 mg of glycerol, and continue stirring at 600 rpm for 10 min until homogeneous. Obtain the mixed film solution. Take 18 mg of the Cu-ZIF-8 composite material prepared in Comparative Example 4 and 18 mg of the TiO2@ZIF-8 composite material prepared in Example 1 and add them to the mixed film solution. After ultrasonic treatment for 20 min, stir and disperse at 600 rpm in a 45°C water bath for 30 min to ensure that the composite material is uniformly dispersed in the film-forming substrate solution. Then allow it to stand to remove bubbles to obtain the film-forming solution. The film-forming solution was poured evenly onto a horizontal casting platform mold and dried at a constant temperature of 37°C for 24 hours to allow the solvent to evaporate slowly and the film to form naturally. After drying, the film was peeled off from the casting platform to obtain the TiO2@ZIF-8 / Cu-ZIF-8 composite film, denoted as GP / TZ+CZ. Performance testing
[0045] (1) Evaluation test of reactive oxygen species (ROS) generation level The reactive oxygen species (ROS) generation levels of the material and film samples were quantitatively evaluated using the 2',7'-dichlorodihydrofluorescein diacetate (DCFH-DA) fluorescent probe method. The material samples were ZIF-8, TiO2+ZIF-8 (physical mixture), TiO2@ZIF-8, TiO2@Cu-ZIF-8 (L), TiO2@Cu-ZIF-8 (D), and Cu-ZIF-8. The film samples were compared with those in Test Example 2, with PBS (phosphate buffered saline) as a blank control.
[0046] Depend on Figure 3As can be seen from the results, the fluorescence intensity of TiO2@Cu-ZIF-8(D) after standing in the dark for 20 min is basically consistent with that of the (PBS) blank control group, indicating that the TiO2@Cu-ZIF-8 composite material prepared in this invention does not generate ROS under light-free conditions and has good dark stability. The ROS level of TiO2@Cu-ZIF-8(L) significantly increased after irradiation with visible light (LED) for 20 min, indicating that the generation of ROS by TiO2@Cu-ZIF-8 requires visible light excitation and exhibits photocontrolled characteristics. This characteristic can avoid the potential negative impact of membrane materials on food quality under light-free conditions in practical applications. Furthermore, comparing the fluorescence intensity of the three groups of samples—ZIF-8, TiO2+ZIF-8 (physical mixture), and TiO2@ZIF-8—it was found that the ROS generation capacity of the TiO2@ZIF-8 group was significantly better than that of the TiO2+ZIF-8 (physical mixture) group. This indicates that the in-situ synthesis method enabled the formation of a tight interfacial contact between TiO2 and ZIF-8 to construct a highly efficient heterojunction structure, which is beneficial for the separation and migration of photogenerated electron-hole pairs, thereby significantly improving the photocatalytic activity of the composite material. In addition, the fluorescence intensity of the TiO2@Cu-ZIF-8 group showed significantly higher ROS generation capacity than the TiO2@ZIF-8 group and the Cu-ZIF-8 group, confirming that the incorporation of Cu²⁺ further increased the photo-redox activity of the TiO2@Cu-ZIF-8 composite material. This is attributed to Cu²⁺. 2+ The defect levels introduced by doping in the band gap of ZIF-8 effectively reduced the energy barrier of photoexcitation and promoted the generation and separation of photogenerated carriers. Furthermore, it confirmed that the heterojunction structure formed between TiO2 and ZIF-8 significantly improved the ROS generation level of the TiO2@Cu-ZIF-8 composite material.
[0047] Depend on Figure 3 As shown in b, GP produces almost no ROS under illumination, and its fluorescence intensity is not significantly different from that of the PBS blank control group, indicating that the gelatin-polyvinyl alcohol membrane matrix itself does not possess the ability to photocatalyze ROS generation. The GP / Z film exhibits weak ROS generation under illumination, which may be due to the ZIF-8 being excited by a small amount of ultraviolet light. The ROS generation ability of the GP / TZ film is significantly enhanced, attributed to the introduction of the TiO2@ZIF-8 heterojunction, which endows the composite film with a certain degree of photocatalytic activity under visible light excitation. The ROS generation ability of the GP / TCZ film reaches the highest level among all film groups, and its fluorescence intensity is approximately twice that of the GP / TZ film, indicating that Cu... 2+Doping significantly enhances the overall photodynamic activity of the composite film; however, the fluorescence intensity of the GP / TCZ dark group is basically consistent with that of the GP group and the PBS blank control group, further confirming that the ROS generation of the composite film of this invention has strict light-controlled characteristics, that is, ROS can only be generated under light conditions and remains inert under dark conditions. In summary, the TiO2@Cu-ZIF-8 photodynamic antibacterial and preservation composite film prepared by this invention has excellent ROS generation ability under visible light irradiation, and can be precisely controlled by light irradiation, providing a reliable ROS source guarantee for achieving safe and controllable photodynamic antibacterial and preservation functions.
[0048] (2) Determination of Cu / Zn ion migration This invention employs inductively coupled plasma mass spectrometry (ICP-MS) to determine the isotopes 63Cu and 66Zn. Each sample is measured in triplicate, and the average signal value is used to calculate the concentration. The mass fractions of Cu and Zn in TiO2@ZIF-8+Cu-ZIF-8 materials, Cu-ZIF-8 composite materials, TiO2@ZIF-8 composite materials, and TiO2@Cu-ZIF-8 composite materials, as well as their migration amounts under simulated food contact conditions (placed in 20 ml of deionized water, ultrasonically homogenized, and stirred for 30 min), are systematically measured to evaluate the biosafety and food contact suitability of the materials. The experimental parameters are as follows: instrument RF power 1.55 kW, RF matching voltage 1.80 V, cooling gas flow rate 15.0 L / min, auxiliary gas flow rate 1.50 L / min, carrier gas flow rate 0.71 L / min, compensation gas flow rate 0.48 L / min, sample rise time 45 s, stabilization time 30 s, and integration time per mass number 0.90 s.
[0049] The Cu / Zn ion migration measurement results showed that the TiO2@Cu-ZIF-8 composite material exhibited Cu ion migration under simulated food contact conditions. 2+ The migration concentration was 0.934 mg / L and Zn 2+ The migration concentration was 2.285 mg / L, and the Cu in the Cu-ZIF-8 composite material was... 2+ The migration concentration was 0.9512 mg / L and Zn 2+ The migration concentration of Zn in the TiO2@ZIF-8 composite material was 2.868755 mg / L. 2+ The migration concentration was 3.66464 mg / L. The composite material Cu formed by the physical mixing of TiO2@ZIF-8 and Cu-ZIF-8 was... 2+ The migration concentration was 1.106 mg / L and Zn 2+The migration concentration was 3.03165 mg / L. The above migration measurement results were compared with the specific migration limits (SML) for metal elements specified in Appendix C of GB9685-2016 "National Food Safety Standard for Additives Used in Food Contact Materials and Articles". The Cu content in the TiO2@Cu-ZIF-8 composite material of this invention... 2+ The migration amount, after conversion, is approximately 0.934 mg / kg, far below the limit requirement of 5 mg / kg; Zn 2+ The migration amount is approximately 2.285 mg / kg, far below the limit requirement of 25 mg / kg, and also far below the Zn content in ZIF-8 materials prepared by traditional methods. 2+ Migration amount. This further illustrates that the content of metal ions migrating in the TiO2@Cu-ZIF-8 composite material described in this application is extremely low during actual fruit and vegetable preservation applications, thus ruling out the possibility that the highly efficient antibacterial effect is due to Zn. 2+ and Cu 2+ Caused by.
[0050] (3) Antibacterial activity The antibacterial properties of material and film samples against Escherichia coli and Staphylococcus aureus were evaluated using the single colony method, while the antibacterial properties against Botrytis cinerea were evaluated using the inhibition zone method.
[0051] Take 20 μL of a concentration of 10 6 CFU / mL bacterial suspension (Escherichia coli or Staphylococcus aureus) was dropped into the center of a thin-film sample, then covered with another identical thin-film sample, trapping the bacterial suspension between the two films (or adding 2 mL of the material sample dispersion). A 5 mm radius Botrytis cinerea mycelium was also trapped between the two films (or adding 2 mL of the material sample dispersion). The light group was placed under an LED white light source, while the dark group was completely wrapped in aluminum foil to avoid light. Both treatment groups were treated at 25°C for 30 min. For bacteria, 100 μL of the reaction bacterial suspension was spread evenly, and for fungi, the solution was drained and inverted onto a plate. Escherichia coli or Staphylococcus aureus were incubated at 37°C for 12 h before observation, while Botrytis cinerea was incubated at 27°C for 36 h before observation.
[0052] Depend on Figure 4It was found that the number of Escherichia coli and Staphylococcus aureus colonies was significantly reduced after treatment with TiO2@Cu-ZIF-8 composite material. The visible light irradiation group showed an antibacterial rate of 99.9% against both bacteria, with colony counts approaching zero. Simultaneously, for Botrytis cinerea, the colony diameter in the blank control group was 6.2 cm, which decreased to 3.2 cm after visible light irradiation with TiO2@Cu-ZIF-8 composite material, while the colony diameter in the dark treatment group was 4.0 cm, indicating limited antibacterial effect. However, both TiO2@ZIF-8 and Cu-ZIF-8 materials showed significant bacterial colony growth under both dark and visible light irradiation conditions, and the colony diameter of Botrytis cinerea in both materials was significantly larger than that of TiO2@Cu-ZIF-8 composite material. The antibacterial results indicate that TiO2@Cu-ZIF-8 composite material exhibits superior broad-spectrum antibacterial performance under visible light excitation. Combined with ICP-MS results (Cu... 2+ The migration amount was 0.934 mg / L, Zn 2+ The migration amount was 2.285 mg / L, which ruled out the possibility that metal ion dissolution played a dominant role in the bactericidal effect. This further proves that the TiO2@Cu-ZIF-8 composite material kills pathogenic microorganisms by efficiently generating ROS under visible light excitation. Its antibacterial mechanism is photodynamic action rather than metal ion release.
[0053] Regarding the antibacterial activity of the film samples, GP showed no significant antibacterial activity against Escherichia coli and Staphylococcus aureus, with colony numbers comparable to the blank control group. Under visible light irradiation, the GP / TCZ composite film achieved a 99.8% inhibition rate against both Escherichia coli and Staphylococcus aureus, with a significant reduction in colony numbers. However, for Botrytis cinerea, the colony diameter in the blank control group was 5.8 cm, while the colony diameter in the GP / TCZ visible light irradiation group decreased to 3.0 cm, and the colony diameter in the GP / TCZ dark treatment group was 5.3 cm. This indicates that the antibacterial effect of GP / TCZ under dark treatment is limited. Furthermore, the antibacterial effect of GP / TZ+CZ is significantly weaker than that of GP / TCZ under both dark and visible light irradiation. This proves that the TiO2@Cu-ZIF-8 photodynamic material, after being incorporated into the GP film matrix, maintains excellent photodynamic antibacterial activity, achieving dual high-efficiency killing of bacteria and fungi under visible light irradiation. Therefore, the TiO2@Cu-ZIF-8 photodynamic antibacterial preservation composite film prepared in this invention can efficiently kill Escherichia coli, Staphylococcus aureus, and Botrytis cinerea through photodynamic mechanism under visible light irradiation. Botrytis cinerea is the main pathogen causing gray mold in strawberries. The significant inhibitory effect of the TiO2@Cu-ZIF-8 photodynamic antibacterial preservation composite film described in this invention provides a direct theoretical basis and experimental support for inhibiting pathogen infection and extending shelf life in post-harvest preservation of strawberries. Example 4
[0054] Application of composite film in strawberry preservation Freshly picked strawberries of uniform size, without mechanical damage and with consistent color were randomly divided into 8 groups, including Control group, GP group, GP / Z group, GP / TZ group, GP / TZ+CZ-D group, GP / TZ+CZ-L group, GP / TCZ-D group, and GP / TCZ-L group. The treatment methods for each group are shown in Table 1.
[0055] Table 1. Treatment methods for 8 groups in the strawberry preservation experiment.
[0056] All groups were stored in an environment with a temperature of 20±1℃ and a relative humidity of 80±1%. Strawberry fruit indicators were tracked and analyzed daily from 0 to 7 days, and visual changes during storage were recorded to systematically evaluate the differences in preservation effects between different groups.
[0057] Depend on Figure 5 It can be seen that the strawberries in all eight treatment groups maintained bright color and plump shape on day 0, with consistent initial quality and no significant differences. As the storage time increased, the strawberries in the Control group began to show slight skin damage and local darkening of color on day 3; the strawberries in the GP, GP / Z, and GP / TZ groups began to show skin damage and slight browning on day 4; and the strawberries in the GP / TCZ-D group began to show signs of skin damage on day 5. This indicates that the TiO2@Cu-ZIF-8 photodynamic antibacterial preservation composite film of the present invention can still delay the deterioration of strawberry quality to a certain extent, even under the condition of no light.
[0058] By day 5 of the storage experiment, all strawberry groups except the GP / TCZ-L group showed varying degrees of rot and mold. The Control and GP groups exhibited the most severe rot, with large areas of gray mold caused by Botrytis cinerea and significant sap exudation on the strawberry surface. The GP / Z and GP / TZ groups showed intermediate levels of rot, but still had visible mold growth points. The GP / TCZ-D group showed slightly less rot than the other dark groups, but still could not prevent mold growth. By day 6, except for the GP / TCZ-L group, all other strawberry groups showed obvious mold colonies on the surface, the fruit color was severely darkened, and some fruits had softened. By day 7, the GP / TCZ-L group strawberries still maintained a relatively bright red color, the fruit shape was plump, and there were no obvious mold spots or signs of rot on the surface, showing the least change in quality compared to the initial quality on day 0. Therefore, the results of the strawberry preservation test fully demonstrate that the TiO2@Cu-ZIF-8 photodynamic antibacterial preservation composite film of this invention can be effectively activated under visible light irradiation. Through photodynamic action, it continuously generates ROS, significantly reducing the concentration of foodborne pathogens (especially fungi such as Botrytis cinerea) in the packaging environment, effectively inhibiting the growth and infection of microorganisms on the strawberry surface, thereby greatly reducing the risk of strawberries spoiling due to pathogen infection. Simultaneously, the suitable gas permeability of the composite film allows for the removal of water vapor and CO2 produced by strawberry respiration, preventing excessive humidity and CO2 accumulation inside the packaging. This results in the GP / TCZ-L group of strawberries exhibiting the best preservation quality among all groups, providing solid technical support for fruit and vegetable preservation and its application in the preparation of food preservation materials.
[0059] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Any person skilled in the art can make many possible variations and modifications to the technical solutions of the present invention, or modify them into equivalent embodiments, without departing from the spirit and technical essence of the present invention. Therefore, any simple modifications, equivalent substitutions, equivalent changes, and modifications made to the above embodiments based on the technical essence of the present invention, without departing from the content of the technical solutions of the present invention, shall still fall within the scope of protection of the present invention.
Claims
1. A TiO2@Cu-ZIF-8 photodynamic antibacterial and preservative composite film, characterized in that, It includes the dispersed phase of TiO2@Cu-ZIF-8 photodynamic material and the continuous phase of the film matrix.
2. The TiO2@Cu-ZIF-8 photodynamic antibacterial and preservative composite film according to claim 1, characterized in that, The preparation method of the dispersed phase of the TiO2@Cu-ZIF-8 photodynamic material includes the following steps: Preparation of S1.TiO2@ZIF-8 composite material 2-Methylimidazole, triethanolamine and anatase nano-TiO2 were dispersed in water to obtain a mixed solution. Zinc acetate dihydrate solution was then added, and the mixture was stirred, aged, centrifuged, washed and freeze-dried to obtain TiO2@ZIF-8 composite material. S2. Copper ion substitution doping TiO2@ZIF-8 composite material was dispersed in water and copper acetate monohydrate solution was added. The mixture was stirred and reacted in the dark. After centrifugation, washing, and freeze-drying, TiO2@Cu-ZIF-8 composite material was obtained.
3. The TiO2@Cu-ZIF-8 photodynamic antibacterial and preservative composite film according to claim 2, characterized in that: The amount of triethanolamine added in S1 is greater than 250 mL / L, and the amount of anatase nano-TiO2 added is 0.5-5.5 g / L, based on the volume of the mixed solution.
4. The TiO2@Cu-ZIF-8 photodynamic antibacterial and preservative composite film according to claim 2, characterized in that: The mass ratio of TiO2@ZIF-8 composite material to copper acetate monohydrate in S2 is 2:(0.5-1.5), and the concentration of TiO2@ZIF-8 composite material is 7.5-9.0 g / L.
5. The TiO2@Cu-ZIF-8 photodynamic antibacterial and preservative composite film according to claim 1, characterized in that, The method for preparing the continuous phase of the membrane matrix is as follows: a gelatin solution and a polyvinyl alcohol solution are mixed to obtain a mixed membrane solution, and then glycerol is added and stirred to obtain the final product.
6. The TiO2@Cu-ZIF-8 photodynamic antibacterial and preservative composite film according to claim 5, characterized in that, The mass ratio of gelatin to polyvinyl alcohol in the mixed film solution is 1:(1-3); the amount of glycerol added is 0.8-1%, based on the total mass of gelatin and polyvinyl alcohol.
7. The TiO2@Cu-ZIF-8 photodynamic antibacterial and preservative composite film according to claim 1, characterized in that, The TiO2@Cu-ZIF-8 photodynamic antibacterial and preservative composite film is prepared by adding 1-6 wt% TiO2@Cu-ZIF-8 composite material to the continuous phase of the film matrix, mixing it evenly, and then casting it into a film.
8. The application of the TiO2@Cu-ZIF-8 photodynamic antibacterial and food preservation composite film according to any one of claims 1-7 in the preparation of food preservation materials.